ANALISIS PERILAKU NASABAH DALAM MENABUNG PADA BMT RAUDHAH MEDAN - Ali Mahadi Ritonga; Khairina Tambunan (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Research conducted to see and find out how customers behave in saving at Baitul Mal Wat Tamwil Raudhah Medan. Research conducted using descriptive qualitative methods to interpret or examine the phenomena that occur. With the subject of research in this study is a customer from BMT Raudhah himself. From the results of the research conducted, there are several conclusions that researchers can conclude including: 1) customers need a lot of consideration in taking the decision to save at this financial institution for reasons of trust, 2) In making this decision, customers have gone through several processes such as recognizing needs, looking for various information, evaluation, decisions in saving, and evaluation after saving, 3) customer decisions to save at BMT Raudhah are based on customer trust in the manager of financial institutions, namely Islamic boarding schools Ar-Raudhatul Hasanah, , 4) in addition to these factors, service to customers also makes the reason or behavior of customers to make decisions to save at BMT Raudhah.